THE DIFFERENCE BETWEEN THE PROSOCIAL TENDENCY REGULAR CLASSES AND SPECIAL CLASSES AT SMAN 1 AND SMAN 3 SEMARANG - Zaldhi Yusuf Akbar; Anita Listiara (Faculty of Psychology, Diponegoro University, 2012)
Prosocial behavior as a form of social concern for the environment, including the look thinner in education, especially in grade specific and regular classes at SMAN 1 and SMAN 3 Semarang. This study aims to determine whether there is any difference between student prosocial tendencies regular classes with high school students a special class consisting of students and an Olympic-class acceleration in Semarang. The hypothesis of this study is that there are differences between students' prosocial tendencies regular classes and special classes of students.This study used a convenient sampling technique for a special class population stands at 103 and 128 regular classroom. The data was collected prosocial tendencies scale consisting of 39 items (reliability coefficient = 0.920). Data analysis was performed with a statistical test of independent samples t test. Based on the obtained value difference test t = -0.491 with p = -0.624 (p> 0.005). Mean of 121.94 while the regular students Mean Grade special for 122.62. Descriptively, this figure means that there are differences in prosocial tendencies, but no significant relationship between students' regular classes and special classes of students.The results of this study illustrate that the regular class students and students of special classes have a level of prosocial tendencies, but not significantly different scores because although special class students have less time because of busy but the attention of the school and the student's ability at SMAN 1 and SMAN 3 Semarang makes no difference prosocial tendencies, but no significant relationship between students' regular classes and special classes of students of SMAN 1 and SMAN 3 Semarang.